Study of the Urgency of Islam as a Religion in the Current of Modernity - Arditya Prayogi; Riki Nasrullah (PT Syamilah Literasi Islami, 2024)
Religion, as a belief system and value system, continues to race against time to always adapt and update its beliefs, values ​​and institutional tools in dealing with new situations in the current modern era so that its owners do not want to be abandoned. The biggest religious challenge in the current of modernization is that truth is no longer always referred to God's law because in this modern era everything can be realized and can be proven with science where there is a condition of people's helplessness to refuse to consume various new products This article aims to provide an overview of the importance of Islam as a religion in today's modern era. This article was written using a qualitative approach supported by literature study methods based on data mining through library research from several literature sources. From the results of the study, it is clear that Islam still has a very important role and cannot be replaced by technology in the modern era. In this case, Islam can play the role of being a fortress for modern human life. Islam teaches its followers various solutions to answer the problems of modern human life. Islam makes its adherents aware that the practice of worship (in the broadest sense) is to be carried out sincerely without seeing that it is an obligation. This ensures that the phenomenon of modern life which erodes human faith is not a reason not to try to improve it, but instead makes this current of modernity a reference for continuing to increase piety.